2013
DOI: 10.1371/journal.pone.0066962
|View full text |Cite
|
Sign up to set email alerts
|

Enduring Effects of Early Life Stress on Firing Patterns of Hippocampal and Thalamocortical Neurons in Rats: Implications for Limbic Epilepsy

Abstract: Early life stress results in an enduring vulnerability to kindling-induced epileptogenesis in rats, but the underlying mechanisms are not well understood. Recent studies indicate the involvement of thalamocortical neuronal circuits in the progression of kindling epileptogenesis. Therefore, we sought to determine in vivo the effects of early life stress and amygdala kindling on the firing pattern of hippocampus as well as thalamic and cortical neurons. Eight week old male Wistar rats, previously exposed to mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 70 publications
(86 reference statements)
3
9
0
Order By: Relevance
“…In addition, these kindling‐induced firing patterns are most prominently observed in the TRN and VPM, with only relatively mild changes seen in the hippocampus and the somatosensory cortex. These findings, which are consistent with those found in another study of neuronal firing patterns in kindled NEC rats, supports the hypothesis that the thalamus facilitates the relay and distribution of seizure activity to neocortical areas in the secondary generalization of limbic seizures …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, these kindling‐induced firing patterns are most prominently observed in the TRN and VPM, with only relatively mild changes seen in the hippocampus and the somatosensory cortex. These findings, which are consistent with those found in another study of neuronal firing patterns in kindled NEC rats, supports the hypothesis that the thalamus facilitates the relay and distribution of seizure activity to neocortical areas in the secondary generalization of limbic seizures …”
Section: Discussionsupporting
confidence: 92%
“…These findings, which are consistent with those found in another study of neuronal firing patterns in kindled NEC rats, supports the hypothesis that the thalamus facilitates the relay and distribution of seizure activity to neocortical areas in the secondary generalization of limbic seizures. 40 Possible underlying mechanisms for the observed descriptive findings of TRN induced by kindling in NEC rats need further experimental exploration. It has been shown that calcium currents are involved in kindling epileptogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The current study was designed to investigate whether this mutation also played a mechanistic role in the resistance to kindling progression phenotype seen in GAERS. Although the F2 rats did not show significant differences in the progression of kindling, we did find that at the single neuronal level the F2 rats homozygous for the R1584P Ca v 3.2 mutation (PP) showed a resistance to developing the low‐frequency burst firing pattern that is associated with kindling progression . In line with our findings, gain‐of‐function mutations in the Ca v 3.2 T‐type Ca 2+ channel have been shown to increase seizure susceptibility of cultured neurons by increasing the spontaneous firing rate .…”
Section: Discussionsupporting
confidence: 85%
“…Different firing parameters were defined to quantify the neural firing patterns in ictal and interictal periods. Five parameters were used to evaluate neuronal firing patterns: (1) mean action potential (AP) firing frequency, (2) percentage of APs in burst, (3) mean number of APs per burst, (4) maximum number of APs per burst, and (5) intraburst frequency as described previously …”
Section: Methodsmentioning
confidence: 99%
“…Five parameters were used to evaluate neuronal firing patterns: (1) mean action potential (AP) firing frequency, (2) percentage of APs in burst, (3) mean number of APs per burst, (4) maximum number of APs per burst, and (5) intraburst frequency as described previously. 15,16 Parameters for characterization of cell firing patterns in ictal periods were the following: (1) the number of APs firing per SWD and (2) the percentage of action potentials firing in burst during SWDs. We also evaluated EEG data to determine the effect of NPY on SWDs including total length, mean duration of SWDs, and cycle frequency.…”
Section: Data Acquisition and Analysismentioning
confidence: 99%